Effects of short term altitude training and tapering on left ventricular morphology in elite swimmers - Haykowsky, M. J.; Smith, D. J.; Malley, L.; Norris, S (Canadian Journal of Cardiology, 1998)
Short or long term athletic training has been associated with left ventricular (LV) morphological adaptations, including increases in wall thickness, cavity dimension and estimated LV mass. A limitation of previous studies assessing the `athlete heart` was that exerciseing was performed at sea level. Since the 1968 Olympic summer games a popular method of maximizing athletic performance has been to use altitude training (AT) as a means of improving sea level performance. However, the effects of short term AT and taper training on LV morphology have not been well studied. Based on this limitation, the effects of three weeks of intense AT (1848 m) or low level control training (CT) (1050 m) followed by two weeks of taper training were investigated in 15 elite swimmers between 16 and 21 years of age. Short term AT or CT training followed by two weeks of taper training was not associated with alterations in LV diastolic cavity dimension (AT pre 53.3±2.8 mm versus post 52.6±4.3 mm; CT pre 52.9±3.7 mm versus post 51.2±4.0 mm), ventricular septal wall thickness (AT pre 9.6±1.0 mm versus post 9.4±1.1 mm; CT pre 8.4±1.2 mm versus post 8.6±1.1 mm), estimated LV mass (AT pre 186.4±45.8 g versus post 190.0±48.2 g; CT pre 159.1±35.8 g versus post 160.1±40.8 g) or fractional shortening (AT pre 36.8±3.5% versus post 34.8±2.7%; CT pre 32.6±5.0% versus post 32.8±4.7%). However, a main time effect, independent of training intervention, was observed for posterior wall thickness (pre 8.7±1.4 mm versus post 9.3±1.1 mm, P<0.05). Therefore, with the exception of osterior wall thickness, short term AT followed by two weeks of taper training appears not to be associated with alterations in LV morphology or systolic function.